Relating Pitch Awareness to Phonemic Awareness in Children: Implications for Tone-Deafness and Dyslexia - Loui, Psyche; Kroog, Kenneth; Zuk, Jennifer; Winner, Ellen; Schlaug, Gottfried (Frontiers in Psychology, 2011)
Language and music are complex cognitive and neural functions that rely on awareness of one’s own sound productions. Information on the awareness of vocal pitch, and its relation to phonemic awareness which is crucial for learning to read, will be important for understanding the relationship between tone-deafness and developmental language disorders such as dyslexia. Here we show that phonemic awareness skills are positively correlated with pitch perception-production skills in children. Children between the ages of 7 and 9 were tested on pitch perception and production, phonemic awareness, and IQ. Results showed a significant positive correlation between pitch perception-production and phonemic awareness, suggesting that the relationship between musical and linguistic sound processing is intimately linked to awareness at the level of pitch and phonemes. Since tone-deafness is a pitch-related impairment and dyslexia is a deficit of phonemic awareness, we suggest that dyslexia and tone-deafness may have a shared and/or common neural basis.